The Mid-Term Evaluation of the National Development Plan and Community Support Framework for Ireland, 2000 to 2006: Final Report to the Department of Finance - (:unkn) unknown (ESRI, 2003)
This is the Final Report on the Mid-Term Evaluation of the National Development Plan (NDP) and the Community Support Framework (CSF) for Ireland for the period 2000-2006. The Report was commissioned by the NDP/CSF Evaluation unit on behalf of the Department of Finance and the EU Commission. The purpose of the mid-term evaluation process is to provide an independent analysis of the Operational Programmes (OPs) of the NDP/CSF and the developments in the external environment since the current plan started in 2000. On the basis of this analysis recommendations are made on how the programmes can be better targeted over the rest of the planning period through a reallocation of funding. The National Development Plan (NDP) is the governments investment programme for the period 2000 to 2006. It covers most major investment by the State in physical capital (buildings and equipment) as well as a significant part of the States investment in education and training and research and development. The Community Support Framework (CSF) is the subset of Measures within the NDP, which are co-funded by the EU Structural Funds. The CSF covers all the EU Structural Fund payments to Ireland but, of course, excludes schemes funded as part of the Common Agricultural Policy (CAP). While the CSF funded investment is still substantial, the bulk of the expenditure under the NDP is not co-funded by the EU. For the first three years of the NDP 2000-2002 approximately 14 per cent of the total expenditure of 19.8 billion was accounted for by the CSF, with the EU contribution amounting to almost 1.7 billion or around 8.6 per cent of total NDP expenditure. The expenditure under the NDP over the three years averaged around 6.8 per cent of GNP a year, of which the direct EU contribution averaged 0.6 per cent of GNP. By EU standards this is a very substantial programme of public investment in both physical and human capital.